Ghana agriculture : its economic development from early times to the middle of the twentieth century - La Anyane, S. (London : Oxford University Press, 1963)
The book attempts to chronicle the history of the development of agriculture in Ghana from the beginning of the nation. It examines the interplay between agricultural development and the prosperity of a nation or otherwise throughout the years.
Includes index.
Includes bibliographical references.
lje 14/06/2017
Loans
Keywords: Agriculture-Economic aspects; Ghana